Fluid-solid interactions in upstream oil and gas applications - Hussein, Ibnelwaleed A.; Mahmoud, Mohamed (Elsevier, 2023)
Fluid-Solid Interactions in Upstream Oil and Gas Applications, Volume 78 delivers comprehensive understanding of fluid-rock interactions in oil and gas reservoirs and their impact on drilling, production, and reservoir hydrocarbon management. The book is arranged based on intervals of the oil and gas production process and introduces the basics of reservoir fluids and their properties, along with the rheological behavior of solid-fluid systems across all stages of the reservoir, including drilling processes, acidizing, and fracking. The reference then addresses different application-specific issues, such as solid-fluid interactions in tight reservoirs, the applications of nanoparticles, interactions during the EOR processes, and environmental concerns.
Keywords: Hydrocarbon reservoirs.; Petroleum -- Geology.; elektronické knihy; electronic books